Essential medicines and human rights: what can they learn from each other? - Hans V Hogerzeil
Most countries have acceded to at least one global or regional covenant or treaty confirming the right to health. After years of international discussions on human rights, many governments are now moving towards practical implementation of their commitments. A practical example may be of help to those governments who aim to translate their international treaty obligations into practice. WHO's Essential Medicines Programme is an example of how this transition from legal principles to practical implementation may be achieved. This programme has been consistent with human rights principles since its inception in the early 1980s, through its focus on equitable access to essential medicines. This paper provides a brief overview of what the international human rights instruments mention about access to essential medicines, and proposes five assessment questions and practical recommendations for governments. These recommendations cover the selection of essential medicines, participation in programme development, mechanisms for transparency and accountability, equitable access by vulnerable groups, and redress mechanisms.